CD14+ blood monocytes can differentiate into functionally mature CD83+ dendritic cells. - Zhou, L J (1996)
Dendritic cells are potent antigen-presenting cells that initiate primary immune responses. Although dendritic cells derive from bone marrow stem cells, the intermediate stages in their development remain unknown. In this study, plastic-adherent blood monocytes (CD14+, CD1a-) cultured for 7 days with granulocyte-monocyte colony-stimulating factor, interleukin 4, and tumor necrosis factor alpha were shown to differentiate into CD1a+ CD83+ dendritic cells. These cells displayed all phenotypic and morphologic characteristics of mature dendritic cells and were the most potent stimulatory cells in allogeneic mixed leukocyte reactions. The identification of specific culture conditions that generate large numbers of dendritic cells from purified monocytes uncovers an important step in dendritic cell maturation that will allow the further characterization of their role in autoimmune diseases, graft rejection, and human immunodeficiency virus infection.